PENGARUH KUALITAS PELAYANAN, BIAYA PENDIDIKAN, DAN KELOMPOK REFERENSI TERHADAP KEPUTUSAN MAHASISWA PENDIDIKAN EKONOMI MEMILIH PADA PROGRAM STUDI PENDIDIKAN EKONOMI - Supardin Supardin; Ninik Indawati; Walipah Walipah (Jurnal Riset Pendidikan Ekonomi, 2019)
This research is a quantitative approach. With explanatory type research. The study population was students of economic education class of 2015-2018 Faculty of Economics and Business, University of Kanjruhan Malang. Sampling using proportional random sampling technique with a sample of 62 students. Data collection techniques using questionnaires and documentation. Analysis of the data used is multiple linear analysis. The results showed that: (1) the quality of service, the cost of education, and the reference group jointly had a positive effect on student decisions, with an F value of 14,623 and a significance level of 0,000. (2) the quality of service has a positive effect on student decisions, with a t value of 6,039, and a significance level of 0,000. (3) the cost of education has an effect on student decisions, with a tcount of -2.093 and a significance level of 0.041. (4) the reference group has a positive effect on student decisions, with a t value of 2.172 and a significance level of 0.034. R2 Test The value of the determinant coefficient (R Square) shows R2 of 43.1%, while the remaining 56.9% is affected by other factors outside the variables of this study